The Alliance Report - Alliance Quebec (AQ) (1987)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1987)

QFHSA Fall Conference 1987 - Quebec Federation of Home and School Associations (QFHSA) (1987)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1987)

Submission to Special Joint Committee on the 1987 Constitutional Accord - Quebec Federation of Home and School Associations (QFHSA) (1987)
The Quebec Federation of Home & School Associations (QFHSA) is pleased to have the opportunity to make this submission to the Special Joint Committee on the 1987 Constitutional Accord.

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1987)

1987 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1987)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1987)

Brief on Health Services in the School Prepared by Quebec Federation of Home & School Associations - Quebec Federation of Home and School Associations (QFHSA) (1987)
Quebec Federation of Home & School Associations (QFHSA), founded in 1944, is an independent, voluntary, parental organization representing approximately five thousand families, mainly within the English speaking communities throughout the province. Parent volunteers are active within local Home & School Associations, the provincial organization and, at the national level, through The Canadian Home & School and Parent-Teacher Federation. In addition, QFHSA has an affiliated group membership of 86 School Committees, school boards and teacher associations. Two of the stated aims of the Home & School movement are to obtain the best for each child according to his or her physical, mental, social and spiritual needs, and to assist in forming public opinion favourable to reform and to the advancement of the education and well-being of the child.

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1987)

The Alliance Report - Alliance Quebec (AQ) (1987)